KAWASAN UNGGULAN SUBSEKTOR TANAMAN PANGAN DI KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Erick Gunawan Bahar; Fajar Restuhadi; Arifudin Arifudin (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2024)
One of the steps taken to improve the community's economy in an area is by implementing a regional development strategy based on leading sectors. By detecting and tracing the ability of the food crop sub-sector in a region to realize competitive and high-value agricultural activities so as to provide benefits for increasing regional income. The purpose of this study was to identify which areas are superior in each food crop sub-sector in Tanah Datar District, West Sumatra Province. The population of this study is all time series data for the production of the food crops sub-sector for 5 years, namely in the period 2017 – 2021 obtained from the Central Bureau of Statistics of Tanah Datar Regency. The analytical methods used to determine superior food crop products include the Sectoral Contribution Index (IKS), Growth Ratio Model (MRP), Location Quotient (LQ), Dynamic Location Quotient (DLQ) and Composite Index (IK). The results showed that based on the calculation of the composite index composed of four indicators (IKS, MRP, LQ, DLQ), the leading commodity areas in the food crops sub-sector with high categories included rice commodities in the Districts of Sungai Tarab, North Lintau Buo, Batipuh and Ten Kotos. The corn commodity is found in the Districts of Sungai Tarab, Ten Koto and Rembatan. Soybean commodities are found in Padang Ganting District. The peanut commodity is found in Salimpauh and South Batipuh Districts. Mung bean commodity is found in Padang Ganting District. The cassava commodity is found in the Rambatan District. Sweet potato commodity is found in Pariangan District.